Crossed-beam experiment for the scattering of low- and intermediate-energy electrons from BF3 - Hoshino, Masamitsu (2018)
This work was conducted under the support of the Japanese Ministry of Education, Sport, Culture, and Technology. F.F.S. acknowledges the Portuguese Foundation for Science and Technology (FCT-MEC) for post-doctoral No. SFRH/BPD/68979/2010 grant, and together with PL-V the Nos. UID/FIS/00068/2013 and PTDC/FIS-ATO/1832/2012 grants through FCT-MEC. PL-V also acknowledges his Visiting Professor position at Sophia University, Tokyo, Japan. F.B. and G.G. acknowledge the partial financial support from the Spanish Ministerio de Economia y Competitivided (Project No. FIS 2012-31230).